Caricature and the Irish : satirical prints from the Library of Trinity College Dublin, c.1780 - 1830 - Robinson, Nicholas K. (Four Courts Press Ltd, 2024)
"From the author's extensive collection given to Trinity College in 1996, 105 caricatures, political and social, have been selected that poke fun at the Irish during London's golden age of caricature. Some of them lampoon (or, occasionally, stand up for) celebrated or notorious individuals, among them Edmund Burke, Richard Brinsley Sheridan, the duke of Wellington, John Philpot Curran, Thomas Moore, Viscount Castlereagh and Lady Caroline Lamb. Others target the sturdily built Irish labourers who migrated to London in search of work, and whose undercutting of local wages was much resented. Many prints, too, were published in Dublin, where plagiarism was rife, alleviated occasionally by witty adaptations." --